(untitled) (Journal of Universal Science Research, 2024)
Mathematics plays a crucial role in geodesic works, providing the foundation for accurate measurement and mapping of the Earth’s surface. This article explores the significance of mathematics in geodesy, highlighting its role in various aspects such as surveying, cartography, and geolocation. By understanding the mathematical principles behind geodesic works, professionals can ensure precise and reliable results in their fieldwork.